2005
DOI: 10.1002/cne.20778
|View full text |Cite
|
Sign up to set email alerts
|

Neuron numbers in the sensory trigeminal nuclei of the rat: A GABA‐ and glycine‐immunocytochemical and stereological analysis

Abstract: The volume, total neuron number, and number of GABA- and glycine-expressing neurons in the sensory trigeminal nuclei of the adult rat were estimated by stereological methods. The mean volume is 1.38+/-0.13 mm3 (mean+/-SD) for the principal nucleus (Vp), 1.59+/-0.06 for the n. oralis (Vo), 2.63+/-0.34 for the n. interpolaris (Vip), and 3.73+/-0.11 for the n. caudalis (Vc). The total neuron numbers are 31,900+/-2,200 (Vp), 21,100+/-3,300 (Vo), 61,600+/-8,300 (Vip), and 159,100+/-25,300 (Vc). Immunoreactive (-ir)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 88 publications
4
45
0
Order By: Relevance
“…We currently ignore how many of these cells have an inhibitory function, but in situ hybridization and immunocytochemical staining suggest that GABAergic and glycinergic cells represent a sizeable proportion of these neurons (Fig. 1) Avendano et al, 2005;Zeilhofer et al, 2005). If feedforward inhibition contributes to the angular tuning of projection cells, one would expect local circuit cells to be among the first to respond to vibrissa deflection.…”
Section: Local Circuit Cellsmentioning
confidence: 99%
“…We currently ignore how many of these cells have an inhibitory function, but in situ hybridization and immunocytochemical staining suggest that GABAergic and glycinergic cells represent a sizeable proportion of these neurons (Fig. 1) Avendano et al, 2005;Zeilhofer et al, 2005). If feedforward inhibition contributes to the angular tuning of projection cells, one would expect local circuit cells to be among the first to respond to vibrissa deflection.…”
Section: Local Circuit Cellsmentioning
confidence: 99%
“…Lesion of SpVi projections, although extensive, did not totally suppress whisker-evoked inhibition in the PrV, suggesting that residual inhibition was mediated by local circuit inhibitory neurons within the PrV (Avendaño et al, 2005;Furuta et al, 2008). We examined how pharmacological blockade of inhibition by local injection of gabazine (a GABAa receptor antagonist) and strychnine (a glycinergic receptor antagonist) affects the angular tuning of PrV cells.…”
Section: Origin Of Inhibition-effect Of Gabaergic and Glycinergic Antmentioning
confidence: 99%
“…Prior studies have shown that the PrV contains GABAergic and glycinergic neurons (Avendaño, et al, 2005), and that it also receives profuse inhibitory input from the SpVi (Furuta et al, 2008). We first examined how lesion of the interpolaris input affected the angular tuning of PrV neurons.…”
Section: Origin Of Inhibition-interpolaris Lesionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because variability in section thickness is potentially a significant source of bias, we systematically weighted the contribution of each section to the final number estimate by the number of cells counted in each section (Avendaño et al, 2005). Nevertheless, celloidin sections exhibit a negligible amount of vertical compression and, consequently, low thickness variability within and among sections (Avendaño and Dykes, 1996;West, 1999).…”
Section: Quantitative Studies In Adult Rat Tg In Vivomentioning
confidence: 99%